2015
DOI: 10.1089/ham.2015.0043
|View full text |Cite
|
Sign up to set email alerts
|

Going High with Heart Disease: The Effect of High Altitude Exposure in Older Individuals and Patients with Coronary Artery Disease

Abstract: Levine, Benjamin D. Going high with heart disease: The effect of high altitude exposure in older individuals and patients with coronary artery disease. High Alt Med Biol 16:89-96, 2015.--Ischemic heart disease is the largest cause of death in older men and women in the western world (Lozano et al., 2012 ; Roth et al., 2015). Atherosclerosis progresses with age, and thus age is the dominant risk factor for coronary heart disease in any algorithm used to assess risk for cardiovascular events. Subclinical atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…Abnormalities in the anterior cingulate gyrus have been previously observed in mental disorders such as schizophrenia and depression, while decreased ReHo in the anterior cingulate gyrus has been associated with depression [Xue et al, ]. Interestingly, previous studies have reported that acute high‐altitude exposure may lead to depression and bipolar disorder as well as increase the psychological ratings for these disorders; thus, decreased ReHo in the anterior cingulate gyrus may be a neuroimaging signature for emotional changes caused by chronic high‐altitude exposure [Levine, ]. Several studies have reported that the medial frontal gyrus is associated with executive mechanisms and decision‐making abilities [Lei et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the anterior cingulate gyrus have been previously observed in mental disorders such as schizophrenia and depression, while decreased ReHo in the anterior cingulate gyrus has been associated with depression [Xue et al, ]. Interestingly, previous studies have reported that acute high‐altitude exposure may lead to depression and bipolar disorder as well as increase the psychological ratings for these disorders; thus, decreased ReHo in the anterior cingulate gyrus may be a neuroimaging signature for emotional changes caused by chronic high‐altitude exposure [Levine, ]. Several studies have reported that the medial frontal gyrus is associated with executive mechanisms and decision‐making abilities [Lei et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary heart disease (CHD) is the leading cause of death in older men and women in the western world, and reduced oxygen availability may cause or ex-acerbate symptoms of CHD [1]. A constant oxygen supply is essential for cardiac viability and function.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis gradually progresses with age, and therefore age is a predominant risk factor in coronary artery disease. 8 Hiking, the most popular physical fitness activity, 1,2,4,9,10 has benefits associated with healthy lifestyles and increased longevity. However, a lack of physical fitness, dehydration, excessive exercise intensity, and exposure to altitude can trigger adverse cardiac events in individuals with risk factors.…”
Section: Discussionmentioning
confidence: 99%